Leveraging the benefits of modularity in the provision of integrated solutions: A strategic learning perspective - Anna Salonen; Risto Rajala; Ari Virtanen (Elsevier, 2022)
The purpose of this study is to improve the current understanding of the ways a manufacturer can learn to leverage the benefits associated with modular solution designs in its transition to a solution provider. We find that a modular solution design acts as a key integration mechanism, allowing the provider to orchestrate actors in the supply network for simultaneous exploitation of resources related to the existing solution modules and exploration of new ones. Yet, to implement a modular solution design effectively, the provider needs to engage in strategic learning that improves its ability to explore customers' readiness to adopt new types of solutions, while it develops an ability to deploy the derivative solutions by utilizing the resources related to its core product business. Mastering the co-evolutionary processes of strategic learning that combine elements of explorative and exploitative learning facilitates a pursuit of the industrializer path to service-based growth. For managers, our findings demonstrate the ways a manufacturer may unlock the economies of scale in solution business by leveraging the benefits of a modular solution design.